Skeletal morphology of the early Paleocene plesiadapiform Torrejonia wilsoni (Euarchonta, Palaechthonidae). Issue 128 (March 2019) - Chester, Stephen G.B.; Williamson, Thomas E.; Silcox, Mary T.; Bloch, Jonathan I.; Sargis, Eric J.
Abstract: Plesiadapiforms, like other Paleogene mammals, are known mostly from fossil teeth and jaw fragments. The several families of plesiadapiforms known from partial skeletons have all been reconstructed as arborealists, but differences in postcranial morphology among these taxa indicate a diversity of positional behaviors. Here we provide the first detailed descriptions and comparisons of a dentally associated partial skeleton (NMMNH P-54500) and of the most complete dentary with anterior teeth (NMMNH P-71598) pertaining to Torrejonia wilsoni, from the early Paleocene (late Torrejonian To3 interval zone) of the Nacimiento Formation, San Juan Basin, New Mexico, USA. NMMNH P-54500 is the oldest known partial skeleton of a plesiadapiform and the only known postcrania for the Palaechthonidae. This skeleton includes craniodental fragments with all permanent teeth fully erupted, and partial forelimbs and hind limbs with some epiphyses unfused, indicating that this individual was a nearly fully-grown subadult. Analysis of the forelimb suggests mobile shoulder and elbow joints, a habitually flexed forearm, and capacity for manual grasping. The hip joint allowed abduction and lateral rotation of the thigh and provides evidence for frequent orthograde postures on large diameter supports. Other aspects of the hind limb suggest a habitually flexed thigh and knee with no evidence for specialized leaping, and mobile ankle joints capable of high degrees of inversion and eversion. Although it is likely that some variability exists within the group, analysis of this skeleton suggests that palaechthonids are most like paromomyids among plesiadapiforms, but retain more plesiomorphic postcranial features than has been documented for the Paromomyidae. These observations are congruent with craniodental evidence supporting palaechthonids and paromomyids as closely related within the Paromomyoidea. The skeleton of T. wilsoni also demonstrates that many regions of the postcranium were already well adapted for arboreality within the first few million years of the diversification of placental mammals following the Cretaceous-Paleogene extinction event.